Application of GGBFS and Bentonite to Auto-Healing Cracks of Cement Paste - J J Ekaputri; M S Anam; Y Luan; C Fujiyama; N Chijiwa; D H E Setiamarga (Universitas Islam Sultan Agung, 2018)
Cracks are caused by many factors. Shrinkage and external loading are the most common reason. It becomes a problem when the ingression of aggressive and harmful substance penetrates to the concrete gap. This problem reduces the durability of the structures. It is well known that self – healing of cracks significantly improves the durability of the concrete structure. This paper presents self-healing cracks of cement paste containing bentonite associated with ground granulated blast furnace slag. The self-healing properties were evaluated with four parameters: crack width on the surface, crack depth, tensile strength recovery, and flexural recovery. In combination with microscopic observation, a healing process over time is also performed. The results show that bentonite improves the healing properties, in terms of surface crack width and crack depth. On the other hand, GGBFS could also improve the healing process, in terms of crack depth, direst tensile recovery, and flexural stiffness recovery. Carbonation reaction is believed as the main mechanism, which contributes the self-healing process as well as the continuous hydration progress.